2014
DOI: 10.1016/j.ijintrel.2014.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the common ingroup identity model and acculturation strategies in intercultural communication: American host nationals’ communication with Chinese international students

Abstract: nationals' perceptions of Chinese international students' cultural adaptation strategies and the effects of the strategies on American host nationals' willingness to communicate with the Chinese students. In addition, the current study also examined the indirect effects of the adaptation strategies through American host nationals' perceptions of anxiety in communicating with and social attractiveness of the Chinese students on willingness to communicate with the Chinese students.Four scenarios describing Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Prior intergroup contact literature, (Imamura et al, 2012), indicates Americans in particular tend to hold negative perceptions of immigrants or sojourners who speak English poorly (e.g., incorrect use of grammar, poor pronunciation). However, Imamura and Zhang (2014) found willingness to communicate is heightened in instances of high-linguistic competence and when other communication norms are shared. To further explore this relationship, the current study seeks to understand the conditions in which willingness to communicate with the speaker and willingness to accommodate to the speaker's ethnic group are affected indirectly by accent stereotyping through other measures of intergroup perceptions (i.e., social attractiveness and intergroup communication anxiety).…”
Section: Communication Accommodation Theory and Willingness To Accommmentioning
confidence: 93%
“…Prior intergroup contact literature, (Imamura et al, 2012), indicates Americans in particular tend to hold negative perceptions of immigrants or sojourners who speak English poorly (e.g., incorrect use of grammar, poor pronunciation). However, Imamura and Zhang (2014) found willingness to communicate is heightened in instances of high-linguistic competence and when other communication norms are shared. To further explore this relationship, the current study seeks to understand the conditions in which willingness to communicate with the speaker and willingness to accommodate to the speaker's ethnic group are affected indirectly by accent stereotyping through other measures of intergroup perceptions (i.e., social attractiveness and intergroup communication anxiety).…”
Section: Communication Accommodation Theory and Willingness To Accommmentioning
confidence: 93%
“…Such challenges may limit the cross-cultural experiences between international and American-born students. Recent studies have shown that friendship formation and interactions among American and international students are mutually beneficial to both groups (Buzzelli, 2016;Imamura & Zhang, 2014;Tawagi & Mak, 2015). The purpose of this quantitative correlation study was to examine the relationship between the CQ of American students and their self-reported SDs from their international peers, considering whether political party affiliation is also a predictor of American students' sense of distance from their international peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have revealed that students studying abroad face a variety of sociocultural and emotional problems (Bierwiaczonek, Waldzus, & Zee, 2017;Fahad, 2015;Gautam et al, 2016;Huhn et al, 2016). In a quantitative study, Imamura and Zhang (2014) found that domestic students were more willing to communicate with their Chinese counterparts, only if the latter group was assimilated into the American way of life (Imamura & Zhang, 2014). American students considered assimilation to American culture as speaking with a clear accent, being able to engage in group discussions, and being understood (Imamura & Zhang, 2014; E. J.…”
Section: Sociocultural Challengesmentioning
confidence: 99%
See 2 more Smart Citations